Evaluating the revenue and taxation implications of cannabis legalization in South Africa: Insights from Canada and the United States - Kiran Baldavoo; Shazia Hassen (Economics, Management and Sustainability)
Purpose: This study aims to evaluate the impact of cannabis legalization on revenue mobilization and taxation in South Africa by analyzing the experiences of jurisdictions that have legalized cannabis. Methodology: A qualitative approach was employed, including a literature review and trend analysis. Data from Canada, California, Colorado, and Washington State, where cannabis has been legalized, were analyzed for 2018-2021. Results: The findings demonstrate that cannabis legalization significantly impacts revenue collection and taxation. However, optimal pricing and taxation policies are crucial to capture the illicit market, minimize negative externalities, and ensure industry growth. Legacy growers and previously disadvantaged individuals should be integrated into the legal market. Theoretical Contribution: The study contributes to the theoretical framework of Pigouvian taxation by examining its applicability to the cannabis industry and the challenges posed by illicit markets and product substitutability with alcohol and tobacco. Practical Implications: The study provides recommendations for South African policymakers on taxation policies, market regulation, and inclusive strategies to ensure a successful and sustainable cannabis industry while maximizing revenue mobilization.